Sex differences in the treatment and outcomes of patients hospitalized with ST‐elevation myocardial infarction. Issue 2 (22nd April 2019) - Hannan, Edward L.; Wu, Yifeng; Tamis‐Holland, Jacqueline; Jacobs, Alice K.; Berger, Peter B.; Ling, Frederick S. K.; Walford, Gary; Venditti, Ferdinand J.; King, Spencer B.
Abstract: Objectives: To compare mortality for women and men hospitalized with ST‐elevation myocardial infarction (STEMI) by age and revascularization status. Background: There is little information on the mortality of men and women not undergoing revascularization, and the impact of age on relative male–female mortality needs to be revisited. Methods and results: An observational database of 23, 809 patients with STEMI presenting at nonfederal New York State hospitals between 2013 and 2015 was used to compare risk‐adjusted inhospital/30‐day mortality for women and men and to explore the impact of age on those differences. Women had significantly higher mortality than men overall (adjusted odds ratio [AOR] = 1.15, 95% CI [1.04, 1.28]), and among patients aged 65 and older. Women had lower revascularization rates in general (AOR = 0.64 [0.59, 0.69]) and for all age groups. Among revascularized STEMI patients, women overall (AOR = 1.30 [1.10, 1.53]) and over 65 had higher mortality than men. Among patients not revascularized, women between the ages of 45 and 64 had lower mortality (AOR = 0.68 [0.48, 0.97]). Conclusions: Women with STEMI, and especially older women, had higher inhospital/30‐day mortality rates than their male counterparts. Women had higher mortality among revascularized patients, but not among patients who were not revascularized.